Penyelesaian Perkara Penghinaan Kepada Suku Melayu Menurut Hukum Adat Melayu Riau Kota Dumai - Lestari, Leny; Effendi, Erdianto; Firmanda, Hengki; Susanti, Heni (Universitas Ekasakti, 2024)
In contrast to positive law, customary law does not recognize the distinction between criminal law and civil law. The settlement of cases in the community is carried out by means according to customary law. One of the cases resolved according to Riau Malay customary law was a case of insulting the Malay tribe in Dumai City. Using empirical juridical research methods, based on the results of the study, it was found that the settlement of cases of insults to the Malays was carried out by deliberation and sanctions ranging from light to severe sanctions, namely making yellow rice, slaughtering animals in the form of chickens, goats and buffaloes and disposing of the country which was divided into two, namely disposing of the country within a specified time and disposing of the country that was not determined.